Prognostic value of adiponectin in coronary artery disease: Role of diabetes and left ventricular systolic dysfunction. (August 2016) - Pratesi, Alessandra; Di Serio, Claudia; Orso, Francesco; Foschini, Alice; Bartoli, Nadia; Marella, Andrea; Fumagalli, Stefano; Di Bari, Mauro; Marchionni, Niccolò; Tarantini, Francesca; Baldasseroni, Samuele
Highlights: We enrolled 138 patients with stable coronary artery disease with or without type 2 diabetes. Adiponectin value of >13.2 ng/ml independently predicts a 6-fold increased risk of mortality. Adiponectin is unable to predict the risk of hospitalization for cardiovascular events. Abstract: Objectives: Adiponectin (AD) promotes insulin sensitivity and has anti-atherogenic properties. However, the role of AD on clinical outcomes in coronary artery disease (CAD) is controversial. We analyzed whether AD was an independent predictor of all-cause mortality and hospitalization in patients with CAD. Method: We prospectively enrolled 138 patients with stable CAD, with or without type 2 diabetes and with or without left ventricular dysfunction. A telephone follow-up was conducted to register long term outcomes. Sensitivity/specificity ratio for AD was investigated with ROC analysis and the independent role of AD on outcome was evaluated with Cox regression model of analysis. The survival rate was represented by Kaplan Meyer curves. Results: Of 138 patients, 61 had type 2 diabetes and 71 left ventricular systolic dysfunction (EF < 40%). Median time of follow-up was 1384 days; mortality rate was 18.8% (26 deaths) and hospitalization rate was 47.1% (65 events). Mean concentration of AD was 9.87 ± 7.53 ng/ml; the analysis of the ROC curve identified an AD cut-off level of 13.2 ng/ml (AUC 0.779; p  < 0.0001). Patients with AD >13.2 ng/ml had a significantly higher risk of death (HR = 6.50; 95% CI: 2.40–17.70), but not of cardiovascular hospitalization (HR = 0.87; 95% CI: 0.31–2.44). AD predictivity remained significant also in patients with type 2 diabetes and with left ventricular systolic dysfunction. Conclusion: In stable CAD, an AD value of >13.2 ng/ml independently predicts a 6-fold increased risk of all-cause mortality.